The Dynamics of Tropical Forests of Western Ghats, Kerala, India, with Special Reference to Growth, Structure, Species Distribution and Fragmentation - Menon, A R R (Indian Forester, 2022)
The tropical forest is always changing gradually through interaction of the living ecosystem and the environment; though seems to be static at a given period of time. These changes can be accelerated by anthropogenic effects and the resultant formations are normally unpredictable, but definitely towards the degraded succession stages. The stratification concept in forest is based on difference in tree heights. This difference in heights may be due to site qualities, geographical features, but more prominent due to intrinsic nature of species. The distribution of trees by diameter classes is basic to study tropical forests and is the most accessible and studied information. It is rarely analyzed in detail; in particular, the influence of soils, topography, and altitude has not been studied systematically. It makes possible the assessment of the effects of the main environmental factors on forest architecture. The management and modification of tropical rainforest environments, though aimed at controlling dynamic process within a human life span, must take account of the damage of long term regression or face ultimate catastrophe. The forest dynamics in tropical forest ecosystems are highlighted in the paper. One liner: The forest dynamics with respect to growth, stratification and floristics of tropical forests are highlighted.